Euro-Asian trade: The stepchild in triadic relations takes over - Friedrich Kirchbach (Intereconomics, 1992)
Euro-Asian trade was for a long time by far the weakest link in the triadic chain of economic relationships between Europe, North America and Asia. The development of the EC towards the single market, the opening up of Eastern Europe and the growth of trade within the Asia Pacific region itself have led to the expectation that this link would become even weaker in future. The following article presents evidence to the contrary.
Keywords: 330